Quality of Life of Cancer Patients during Chemotherapy in Indonesia: A Comparison of EORTC QLQ-C30 and EQ-5D-5L, Based on Patients’ Characteristics - Dyah A. Perwitasari; Fredrick D. Purba; Susan F. Candradewi; Haafizah Dania; Lalu Muhammad Irham; Imaniar Noor Faridah; Bayu P. Septiantoro (International Journal of Clinical Practice)
One of the important outcomes to define the success of cancer treatment is the health-related quality of life (HRQoL) that can be measured using generic and/or specific instruments. Our study aims to define the cancer patients’ HRQoL in some hospitals in Indonesia as measured by the European Organization for Research and Treatment for Cancer (EORTC QLQ-C30) and the EQ-5D-5L, to define the differences of cancer patients’ HRQoL referring to patients’ characteristics, and to explore determinants of cancer patients’ HRQoL. We recruited 451 cancer patients using a cross-sectional design in two referral hospitals in Central Java, Indonesia, using the purposive sampling technique. All subjects, recruited from July 2020 to October 2021, met the inclusion criteria, namely, adult patients diagnosed with cancers in all stages who willingly participated in the study. The Indonesian value set was used to obtain the EQ-5D-5L index score. We further analyzed the data based on cancer stages and compared two questionnaires using independent t test. We highlighted that most of the cancer patients are female (69.4%), young (86%), and at advanced stages of cancer (54.1%). The physical and role functions and global health status of the cancer patients are poor, and the most severe symptom is fatigue. Moreover, most of them experience severe pain and perform daily activities with difficulties. Some patients’ characteristics show significant influences on the HRQoL domains in both questionnaires (p<0.05). Interestingly, both of the questionnaires have shown significant correlations between similar domains and revealed the poor HRQoL of advanced cancer patients (p<0.05). Our study finds that cancer patients still have poor HRQoL in some domains. We suggest to the health providers that they apply education and psychological intervention to increase their HRQoL.